PERBAIKAN SANITASI DAN HYGIENE PRODUK BANDENG PRESTO AR PUTRA MAJU JAYA DI DESA TEGAL ARUM, MOJOSONGO, SURAKARTA - Raden Baskara Katri Anandito; Siswanti Siswanti; Lukita Purnamayati; Bara Yudhistira (Jurnal Kewirausahaan dan Bisnis, 2019)
Tegal Arum Village is one of the presto milkfish processing areas in Surakarta. One of the household industries that has been running for a long time with this business is Mr. Darpo's milkfish presto owned by the name IRT "AR Putra Maju Jaya". This business has been initiated since 2015, with production capacity reaching four quintals every day. Fresh milkfish used are imported from Gresik. This IRT has 4 employees who work 6 days a week. The high number of presto milkfish processors in Surakarta results in increasingly fierce business competition. This causes IRT to experience difficulties in expanding the marketing area so that income is stagnant and does not increase. The main problem found in the IRT milkfish presto "AR Putra Maju Jaya" Mr. Darpo is the still low standard of sanitation and hygiene processing, the equipment used is still limited and simple so that the production and storage capacity is minimal, there is no good packaging so the product is less attractive and easily damaged. The solution to these problems is to improve the presto milkfish processing by applying sanitation and hygiene standards by rearranging the production space, helping equipment made of stainless steel, improving product packaging with packaging variations and packaging design as well as adequate raw materials and product storage. The effort is expected to be able to improve the quality of AR Putra Maju Jaya's milkfish presto so that it can increase production capacity and marketing areas.